2016
DOI: 10.3847/0004-637x/832/2/131
|View full text |Cite
|
Sign up to set email alerts
|

EVIDENCE FOR THE DIRECT DETECTION OF THE THERMAL SPECTRUM OF THE NON-TRANSITING HOT GAS GIANT HD 88133 b

Abstract: We target the thermal emission spectrum of the non-transiting gas giant HD 88133 b with high-resolution nearinfrared spectroscopy, by treating the planet and its host star as a spectroscopic binary. For sufficiently deep summed flux observations of the star and planet across multiple epochs, it is possible to resolve the signal of the hot gas giant's atmosphere compared to the brighter stellar spectrum, at a level consistent with the aggregate shot noise of the full data set. To do this, we first perform a pri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 48 publications
2
70
0
Order By: Relevance
“…As in Piskorz et al (2016), all but about 0.1% of the variance in each night's data set is encapsulated by the first principal component. The following results are roughly consistent for data sets with more than the first principal component removed.…”
Section: Extraction Of 1d Spectra and Pca-like Telluric Correctionmentioning
confidence: 92%
See 2 more Smart Citations
“…As in Piskorz et al (2016), all but about 0.1% of the variance in each night's data set is encapsulated by the first principal component. The following results are roughly consistent for data sets with more than the first principal component removed.…”
Section: Extraction Of 1d Spectra and Pca-like Telluric Correctionmentioning
confidence: 92%
“…As in Piskorz et al (2016), at this step, we eliminate the K r and K l band orders ranging from 2.3 to 2.4 μm from the analysis since there is high correlation between the stellar and planetary models themselves at these wavelengths. This means we remove any signal from carbon monoxide, and the dominant molecule in the planetary model in the remaining wavelengths is water vapor.…”
Section: Two-dimensional Cross-correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…We reduced raw data from NIRSEPC using two packages, the IDL-based REDSPEC (Kim et al 2015;Prato et al 2015) and the Python-based PyNIRSPEC (Boogert et al 2002;Piskorz et al 2016). We compared results from the two packages and concluded that the final, calibrated 1-d spectra are similar within measurement uncertainties.…”
Section: Data Reductionmentioning
confidence: 99%
“…This was followed by the detection of CO molecular absorption from the dayside of the non-transiting hot-Jupiter τ Boo b by both Brogi et al (2012) and Rodler et al (2012) (with water vapour later found for the same planet by Lockwood et al 2014). Since these discoveries, additional detections (including for other molecular species such H 2 O and TiO) have also been reported for 51 Peg b Birkby et al 2017), HD189733b (de Kok et al 2013Birkby et al 2013;Brogi et al 2016;Brogi et al 2018), HD179949b (Brogi et al 2014), upsilon Andromedae b (Piskorz et al 2017), HD88133b (Piskorz et al 2016), and WASP-33b (Nugroho et al 2017).…”
Section: Introductionmentioning
confidence: 95%